Recent progress on carbon-based composite materials for microwave electromagnetic interference shielding - Kumar, Rajesh; Sahoo, Sumanta; Joanni, Ednan; Singh, Rajesh K.; Tan, Wai Kian; Kar, Kamal K.; Matsuda, Atsunori (Carbon (New York), 2021)
The demand for electromagnetic interference (EMI) shielding has increased strongly in the last few years, owing to the fast technological developments in the electronics industry. In order to meet these markedly increased demands, many new layer-structured materials (as well as other structures with various morphologies) are being investigated to replace conventionally used metal sheets for the purpose of EMI shielding. Carbon-based nanostructures and their composites are used for EMI protection due to their low weight, cost-effectiveness, and good thermal/electrical properties. Polymers are also low density materials, with the added benefits of low cost and easy processing. Composites combining various polymers with different types of conducting carbon fillers have been proposed as EM wave absorbers. MXene-based 2D layered materials have also received tremendous attention for application in EMI shielding. In this review article, we have systematically summarized the recent research on materials designed for microwave/radio wave absorption and EMI shielding. The text covers carbon-based nanostructured materials, various kinds of polymers, layered inorganic materials and their composite hybrids. The review is concluded with a brief discussion of the perspectives and outstanding challenges for future EMI shielding applications of carbon, polymers and MXene-based materials. The main classes of materials used for EMI shielding and possible attenuation mechanisms for EM waves incident on a slab of EMI shielding material. [Display omitted]